Door-to-needle time for thrombolysis: a secondary analysis of the TIPS cluster randomised controlled trial. Issue 12 (15th December 2019) - Hasnain, Md Golam; Paul, Christine L; Attia, John R; Ryan, Annika; Kerr, Erin; D'Este, Catherine; Hall, Alix; Milton, Abul Hasnat; Hubbard, Isobel J; Levi, Christopher R
Abstract : Objective: The current study aimed to evaluate the effects of a multi-component in-hospital intervention on the door-to-needle time for intravenous thrombolysis in acute ischaemic stroke. Design: This study was a post hoc analysis of door-to-needle time data from a cluster-randomised controlled trial testing an intervention to boost intravenous thrombolysis implementation. Setting: The study was conducted among 20 hospitals from three Australian states. Participant: Eligible hospitals had a Stroke Care Unit or staffing equivalent to a stroke physician and a nurse, and were in the early stages of implementing thrombolysis. Intervention: The intervention was multifaceted and developed using the behaviour change wheel and informed by breakthrough collaborative methodology using components of the health behaviour change wheel. Primary and secondary outcome measures: The primary outcome for this analysis was door-to-needle time for thrombolysis and secondary outcome was the proportion of patients received thrombolysis within 60 min of hospital arrival. Results: The intervention versus control difference in the door-to-needle times was non-significant overall nor significant by hospital classification. To provide additional context for the findings, we also evaluated the results within intervention and control hospitals. During the active-intervention period, the intervention hospitals showed a significant decrease in the door-to-needle time of 9.25 min (95% CI: -16.93 to 1.57), but during the post-intervention period, the result was not significant. During the active intervention period, control hospitals also showed a significant decrease in the door-to-needle time of 5.26 min (95% CI: −8.37 to −2.14) and during the post-intervention period, this trend continued with a decrease of 12.13 min (95% CI: -17.44 to 6.81). Conclusion: Across these primary stroke care centres in Australia, a secular trend towards shorter door-to-needle times across both intervention and control hospitals was evident, however the TIPS (Thrombolysis ImPlementation in Stroke) intervention showed no overall effect on door-to-needle times in the randomised comparison. Trial registration number: Trial Registration-URL: http://www.anzctr.org.au/ Unique Identifier: ACTRN 12613000939796.